Exploring the optimal reconstruction strategy for Enneking III defects in pelvis bone tumors: a finite element analysis - Jiazhuang Zhu; Jianping Hu; Kunpeng Zhu; Xiaolong Ma; Zhen Huang; Chunlin Zhang (Journal of Orthopaedic Surgery and Research)
Abstract Background Controversy exists regarding the reconstruction of bone defects in Enneking III. This study aimed to use the finite element analysis (FEA) method to clarify (1) the utility of reconstructing the pelvis Enneking III region and (2) the optimal approach for this reconstruction. Methods FEA models were generated for three types of Enneking III defects in the pelvis, replacing all the defect areas in region III with a sizable solid box for topology optimization (TO). Based on the defect location and TO results, three reconstruction schemes were designed for each type of defect. We subsequently conducted simulations of static FEA under natural walking loads using ANSYS software (version 2022R1, Canonsburg, Pennsylvania, USA). Results Compared with Scheme A, reconstruction of the Enneking III region (Schemes B and C) led to a more uniform stress distribution and lower peak stress in the pelvis. Moreover, prostheses and screws exhibit decreased peak stress and deformation, with complex reconstruction schemes (C) outperforming simpler ones (B). Conclusions The FEA results suggest that reconstructing Enneking Zone III defects improves stress distribution and reduces peak stress in the pelvis compared to non-reconstruction, potentially enhancing stability and reducing fracture risks. Complex reconstruction schemes involving more contralateral pelvis regions demonstrate superior biomechanical performance. However, clinical decisions should be individualized, integrating biomechanical insights with comprehensive patient-specific factors.